Theoretical study of weak CC double bond coordination in a gold (I) catalyst precursor - Touil, Mhamed; Bechem, Benjamin; Hashmi, A. Stephen K.; Engels, Bernd; Omary, Mohammad A.; Rabaâ, Hassan (Journal of molecular structure, 2010)
MP2, CCSD and DFT/B3LYP modelling were performed to gain insight into CC-Au interaction in the gold precursor [(biphenyl-NMe2)Ph2PAuCl], A. Prior to this work, the existence of CC coordination to the gold (I) center as well as the nature of this precursor structure in the phenol synthesis have remained uncertain. To determine the nature of the bonding in the structure of pre-catalyst A, we carried out different optimizations at different levels of theory. DFT results revealed weak Au-CC bond in models of A, longer than the experimental X-ray bond length, while MP2 and CCSD attained higher accuracy. We also examined other configurations of the Au(I) center in phenol synthesis by computing several hypothetical neutral and cationic complex models. Four structures of related gold model complexes were optimized by several methods. These computations suggest that the cationic pre-catalyst [(biphenyl)PH2Au]+ model leads to a dissymmetric πCC coordination and exhibits greater reactivity than that in the neutral [(biphenyl)PH2AuCl] model. The cationic complex was found to be more favorable than the neutral model from a thermodynamic point of view (computed ΔG). Therefore, we suggest a possible equilibrium in situ between the cationic and neutral forms. We also have carried out geometry optimization for the simplified cationic model [benzene-Au-PH3]+ in order to provide a more accurate assessment of the bond energy and coordination sphere involving the η2-olefin-Au(I) moiety.